Post-Independence Group Reading Communism Via Independent Documentary Soundtracks - Ali, Mohd. Nor Shahizan; Fleming, Dan; Samani, Mus Chairil (2016)
Regarding the issue of independence documentary, the key question that must be considered is whether a message that’s trying to convey to the target groups or audiences are fully achieved? The used of soundtracks to convey the message of independent documentary is seen as the added value for audiences to digest the producers’ idea. Zettl (2005) put the cultural, ideology and technological narrative message of the production based on soundtracks analysis (lyrics as long as costume and make-up) as a part of the narrative in soundtracks). Using an independent documentary ‘The Last Communist (2006)’ work of Amir Muhammad, this article discussed the ‘reading’ of soundtracks. These soundtracks are technically representing producers’ idea. They construct connotation meaning for audiences to read as they want. The soundtracks are highly posed and are set in descript meaning to make them usable across the world.